The Effect Of Education And Training And Teaching Motivation On Junior High School Teacher Job Satisfaction At Tomohon City State - Yongker Baali; Demsi Robert Sasewa; Risma Rosita Pompana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aimed to obtain the results of the study and a description of: (1) The effect of education and training on job satisfaction of teachers of SMP Negeri Tomohon, (2) Effect of motivational teaching on job satisfaction of teachers of SMP Negeri Tomohon, (3) Effects of education and training and motivation to job satisfaction of teachers teaching Junior High School Tomohon. This research was conducted in December 2019 until Februry 2021 with a survey method with quantitative approach using instrument questionnaire on teachers SMP Tomohon city which unit a population of 131 people while the sample of 57 people. The results using statistical analysis was obtained: (1) Education and training affect the job satisfaction of teachers SMP Tomohon. Correlation coefficient (r) of 0.839, which means that education and training (X1) has a strong and positive influence on job satisfaction of teachers (Y). (2) Motivation teaching effect on job satisfaction of teachers SMP Tomohon. Correlation coefficient (r) of 0.535, which means that the motivation of teaching (X2) have a substantial positive influence on job satisfaction of teachers (Y); and (3) Education and training and motivation taught jointly affect the job satisfaction of teachers SMP Tomohon. Correlation coefficient (r) of 0.843, which means education and training (X1) and motivation to teach (X2) together have a strong influence on teacher job satisfaction (Y). Based on the above conclusion, it can be suggested: (1) Continuously headmasters at SMP Negeri Tomohon establish a task in order to provide guidance to teachers there, so the motivation of teaching remains a major when carrying out tasks according to teacher competence , (2) Indicators of job satisfaction of teachers of SMP Tomohon to the attention of the principal nor the parties that are competent in an effort to promote education in Tomohon, (3) continuously, both principals and other school communities need to maintain an atmosphere conducive in providing education in schools. The school principal should maintain a balance between managerial process for generating motivation achievement and school climate and atmosphere that makes no job satisfaction among teachers.